Cookery 9 : technology and livelihood education : modules in home economics by Joana C. Peralta - Peralta, Joana C. (Quezon City : St. Bernadette Publishing House Corporation, 2014)
"This book is compilation of all the necessary lessons which will give an opportunity for developing a enhancing the skills that are needed in cooking". The module starts with the discussion of the Personal Entrepreneur Competencies that a cook should possess as well as the ability to explore for business opportunities. The four units deal with the most important aspects of cooking and the different methods of food preparation that will help a would be entrepreneur start a simple business. The first unit will give training on how to make a cooking environment safe and hygienic, which are very important in food preparation and cooking. the rest of the units will give hands on the actual preparation and cooking of different kinds of food including the choice of ingredients, together with preparation, measurement, cooking, planting or presentation, serving and packaging of some foods. this book was prepared with so much passion, with the intent that it will be of great help to would-be entrepreneur".
English text.
Keywords: Cooking